Determination of the Cascade Reservoir Operation for Optimal Firm-Energy Using Genetic Algorithms - Azmeri -; Iwan K; Hadihardaja -; Sri Legowo (Graduate Program of Syiah Kuala University, 2013)
Abstract - Indonesia today face a new paradigm in water management where aim to apply integrated water resources management has become unavoidable task in purpose of achieving greater level of effectiveness and efficiency. On of most interesting case study is the case of Citarum river, one of the most potential river for water supply in West Java, Indonesia. Alongside the river, Saguling, Cirata and Djuanda Reservoirs had been constructed in series/cascade. Saguling and Cirata reservoirs are particularly operated for hydroelectric power and Djuanda is multipurpose reservoir mainly operated for irrigation and contribute domestic water supply for Jakarta (capital city of Indonesia). Basically all reservoirs are relying on same resources, therefore this condition has considered addressing management and operational problem. Therefore, an approach toward new management and operation system are urgently required in order to achieve the effective and efficient output and to avoid conflicts of water used. This study aims to obtain energy production from Citarum Cascade Reservoir System using Genetic Algorithms optimization with the objective function to maximize firm-energy. Firm-energy is the minimum energy requirements must be available in a certain time period. Then, the result obtained by using the energy produced by GA is compared to the conventional searching technique of Non-Linier Programming (NLP). The GA derived operating curves reveal the higher energy and firm-energy than NLP model. Keywords: Genetic Algorithms, Citarum Cascade Reservoir, Firm-Energy, Electrical Energy